Determination of Germination Properties of Some Alfalfa Cultivars in Different Salt Concentrations - Yılmaz, Mustafa; Bayram, Gamze (Turkish Journal of Agriculture - Food Science and Technology, 2019)
This study was carried out in Sakarya University Food Engineering Department in March 2019 to determine the responses of some alfalfa varieties to different salt concentrations during germination period. As plant material; Azurre, Delta, Emiliano, Emiliano (coated), La Bella Campagnola and Neptune varieties were used. Six different salt concentration levels (0, 50, 100, 150, 200 mmol) were applied in the study. The experiment was set up in a randomized plot design with 2 factors and 3 replicates. In the study; germination percentage, plumule length, radicle length, salt tolerance index, plumule dry weight, radicle dry weight were examined. The results of the research showed that salt concentrations had a statistically significant effect on all investigated properties. It was determined that values obtained in all properties decreased with increasing salt concentration. It was found that Emiliano coated variety was more tolerant than the other varieties in terms of the properties examined among the varieties. It was determined that more than 50 mmol of the salt concentration had a significant negative effect on the properties studied and the lowest values occurred at a dose of 200 mmol. Variety × Salt concentration interactions were examined; The highest salt tolerance index was determined by Emiliano coated × 50 mmol interaction. In this study, it was concluded that Emiliano cultivar may be more tolerant than other cultivars in alfalfa agriculture in soils with salinity problem.